SURVEY ON METEOROLOGICAL WEATHER ANALYSIS BASED ON NAÏVE BAYES CLASSIFICATION ALGORITHM (International Journal of Engineering and Computer Science, 2017)
The aim of this research work, to focuses meteorological data to predict the monsoon seasons to separate the weather data   based on Longitudinal and Latitudinal which can be used to analyse the reliability factor of Temperature, Humidity, Rainfall and Cyclone.The present paper analyses the monthly weather data and rainfall data from the Indian monsoon months between the year 2000 to 2014.To find the relationship between the rainfall details, humidity, temperature, After finding the reliability, Naïve Bayes Classification can be predict the Meteorological condition of region based on the cyclone and humidity level in seasonally. It provides specific services to assessment of pollution impacts from different companies and thermal power plants. The environment correlations play a significant role in determining the climate trends which are crucial in understanding the short and long-term trends in climate.